2012
DOI: 10.1111/j.1525-1314.2012.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2O in the formation of garnet coronas during near‐isobaric cooling of mafic granulites: the Tasiusarsuaq terrane, southern West Greenland

Abstract: The Mesoarchaean Tasiusarsuaq terrane of southern West Greenland consists of Tonalite-trondhjemite-granodiorite gneisses and, locally, polymetamorphic mafic and ultramafic rocks. The terrane experienced medium-pressure granulite facies conditions during M 1A in the Neoarchean, resulting in the development of two-pyroxene melanosome assemblages in mafic granulites containing garnet-bearing leucosome. Reworking of these rocks during retrogression introduced garnet to the melanosome in the form of overgrowths, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 55 publications
0
10
0
3
Order By: Relevance
“…The suturing of the southern five NAC blocks is suggested to have formed by collisional tectonics controlled by SE-dipping subduction zones, and possibly involving the closure of back-arc basins by subduction (Friend and Nutman, 1991;Nutman and Friend 2007;Windley and Garde, 2009). The currently accepted model for the formation of the NAC can be summarised by three overlapping phases: 1) Two protracted TTGforming events at 3.85-3.70 Ga and 3.20-2.82 Ga, attributed to the partial melting of basaltic lithologies such as amphibolite and eclogite (Tappe et al, 2011), which generates proto-blocks of continental crust; 2) a geographically wide-spread and protracted period of metamorphic zircon growth at 3.0-2.7 Ga (Garde et al, 2000) that records the timing of granulite facies metamorphism and the extensive emplacement of granitic rocks with a strong thermal overprint of 850°C at~0.75 GPa, indicating a Mesoarchaean thermal gradient of 1100°C/GPa (Dziggel et al, 2012); and, 3) accretion of island-arc type crustal blocks from the Fiskefjord block and southward, which culminated in the frequently cited (e.g., Baadsgaard and McGregor, 1981) 'Qaarusuk dyke' injection at ca. 2.72 Ga, demarking the end of penetrative Archaean deformation (Friend et al, 1996).…”
Section: Assembly Of the North Atlantic Cratonmentioning
confidence: 98%
“…The suturing of the southern five NAC blocks is suggested to have formed by collisional tectonics controlled by SE-dipping subduction zones, and possibly involving the closure of back-arc basins by subduction (Friend and Nutman, 1991;Nutman and Friend 2007;Windley and Garde, 2009). The currently accepted model for the formation of the NAC can be summarised by three overlapping phases: 1) Two protracted TTGforming events at 3.85-3.70 Ga and 3.20-2.82 Ga, attributed to the partial melting of basaltic lithologies such as amphibolite and eclogite (Tappe et al, 2011), which generates proto-blocks of continental crust; 2) a geographically wide-spread and protracted period of metamorphic zircon growth at 3.0-2.7 Ga (Garde et al, 2000) that records the timing of granulite facies metamorphism and the extensive emplacement of granitic rocks with a strong thermal overprint of 850°C at~0.75 GPa, indicating a Mesoarchaean thermal gradient of 1100°C/GPa (Dziggel et al, 2012); and, 3) accretion of island-arc type crustal blocks from the Fiskefjord block and southward, which culminated in the frequently cited (e.g., Baadsgaard and McGregor, 1981) 'Qaarusuk dyke' injection at ca. 2.72 Ga, demarking the end of penetrative Archaean deformation (Friend et al, 1996).…”
Section: Assembly Of the North Atlantic Cratonmentioning
confidence: 98%
“…6; cf. Dziggel et al, 2012). For the rocks to have replaced their high-T assemblages with the minerals observed in the samples described here, they must have experienced an addition of H 2 O (Fig.…”
Section: Fluid Regime Fluid Source and Infiltration Mechanismsmentioning
confidence: 99%
“…Previous studies on eclogite have demonstrated that the phase relations in these rocks, and the occurrence of overprinting amphibolite or granulite facies assemblages, is a function of not only pressure and temperature but also components such as Fe 2 O 3 (Ague et al, 2001;Chinner, 1960;Clarke et al, 1989;Diener and Powell, 2010;Rebay et al, 2010) and H 2 O (Baldwin et al, 2007;Dziggel et al, 2012;Rebay et al, 2010;Śtĭpskà and Powell, 2005). Rebay et al (2010) quantitatively investigated the role of H 2 O on the stability of eclogite assemblages, and found that these rocks might not form 'true' eclogite facies assemblages under fluid-saturated conditions.…”
Section: Mineral Equilibria Modellingmentioning
confidence: 95%